Egg - Henkes, Kevin (New York : Greenwillow Books, 2017)
Three little birds crack their way out of eggs and fly away, leaving one egg sitting all alone until the three chicks come back and discover a friendly baby alligator has finally hatched.
School Library Journal starred, December 2016
Pub Weekly, October 2016
Kirkus Starred, October 2016
Booklist, October 2016
Bulletin (Center for Children's books), January 2017
K-3
Keywords: Eggs -- Fiction; Birth -- Fiction; Animals -- Infancy -- Fiction; Friendship -- Fiction; Eggs -- Fiction; Animal babies -- Fiction; Friendship -- Fiction